Drug-resistant epilepsy cases in chromosomal pathology - L. B. Novikova; A. P. Akopyan; R. F. Latypova; N. M. Faizullina (Эпилепсия и пароксизмальные состояния)
Two cases of epilepsy in patients with a rare hereditary pathology associated with a chromosomal mutation caused deletion of chromosome 14 are presented. In the first case, this pathology was manifested in the child by generalized tonic-clonic seizures, delayed psycho-verbal development, and facial skull microanomaly. In the second case, it was expressed in tonic epileptic seizures, delayed psycho-verbal development, developmental microanomalies, pyramidal atactic syndrome and hand joint hypermobility. Such clinical observations are of professional and scientific interest, as they relate to a rare neurological pathology, with drug-resistant epilepsy as a leading sign.